Meningkatkan Daya Nalar Kritis melalui Metode PBL dalam Pembelajaran Pendidikan Agama Katolik Siswa Kelas VIII A SMP Negeri 2 Playen - Franciska Arindikha; Anselmus Joko; Roida Roida (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve students' critical thinking skills in Catholic Religious Education through the implementation of Problem-Based Learning (PBL). The subjects of this study were students of class VIIIA at SMP Negeri 2 Playen during the first semester of the 2024/2025 academic year. The research was conducted in two cycles, which included the stages of planning, implementation, observation, and reflection. Data were collected through pre-tests and post-tests, observations, and interviews, and analyzed qualitatively and quantitatively. The results showed that the implementation of PBL significantly improved students' critical thinking skills. In the first cycle, the average pre-test score was 5.3, which increased to 7.2 in the post-test (a 36% increase). However, most students still struggled to relate theological concepts to real-life situations. In the second cycle, the average pre-test score increased to 6.5, while the post-test average reached 8.4 (a 29% increase). Student engagement in group discussions and problem-solving activities also improved, with participation levels increasing from 65% in the first cycle to 85% in the second cycle. The implementation of PBL proved effective not only in developing critical thinking skills but also in helping students deeply understand the material on The Mission and Calling of Jesus’ Disciples and apply religious values in daily life. Therefore, PBL is recommended as a relevant learning method to support the development of critical thinking skills and student engagement in religious education.